Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America - Dolibaina, Diego Rodrigo; Carneiro, Eduardo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins; Lamas, Gerardo (Zootaxa, 2017)
A new species belonging to the previously monotypic genus Panca Evans, 1955, P. moseri Dolibaina, Carneiro & O. Mielke sp. nov., from grasslands areas of Peru, Bolivia and Brazil is described. Adults and male and female genitalia of the new species are illustrated, described in detail, and compared with the type species of the genus, Lerodea subpunctuli Hayward, 1934, and with its externally most similar and sympatric species, Vidius mictra Evans, 1955. The systematic position of the genus Panca and its association with lowland open natural habitats of South America are discussed.